PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BAGI KELOMPOK PKK KECAMATAN KAPUAS KABUPATEN SANGGAU - Pratiwi, Nia; Nugroho, Yohanes Adi; Saputra, Edi; Sastrawan, Rahman; Hendreo, Chornolius; Toliang, Ermina; Ilham, Syarif Muhammad; Maulana, Arief Rio (JURNAL ABDIMAS PLJ, 2023)
The community service activity was initiated by the Accounting Department's PPM team after coordinating with the head of the PKK (Family Welfare Empowerment Program) team in the Kapuas sub-district of Sanggau Regency in August 2023. The coordination and survey results with the head of the PKK team revealed that there had been no previous involvement of the Community Service (PPM) team from the Accounting D-3 Study Program at the PSDKU POLNEP Campus in Sanggau Regency, providing financial report training to the PKK group in the Kapuas sub-district of Sanggau Regency. The PKK group also demonstrated a lack of understanding in the field of accounting and financial reporting. Their level of understanding regarding accounting and financial reports was low, making it difficult for village and neighborhood leaders to compile and explain these financial reports. The solution proposed by the Accounting Department's PPM team to address the issues faced by their partners was to conduct financial report training for the PKK group in the Kapuas sub-district of Sanggau Regency. Through this training, the PKK group would be equipped with knowledge and skills in accounting and financial reporting, particularly in the preparation of financial reports. After identifying the partner's problems, the Accounting Department's PPM team prepared a module for financial report preparation, conducted the training, provided assistance, evaluated the process, and prepared activity implementation reports in the form of a proposal, progress report, and final PPM report. This training took place on Monday, September 11, 2023, at the Kapuas sub-district office hall in Sanggau Regency, with 62 participants from the PKK groups. The training activity went smoothly and was executed as intended, starting at 8:00 AM until completion. Consequently, this training could assist the PKK groups in enhancing their understanding of accounting record-keeping and the accounting processes in preparing financial reports. This activity resulted in mandatory outputs published in an article in the Pontianak Post newspaper on Wednesday, September 13, 2023. Keywords: Accounting, Financial Reporting, PKK Group